The likability trap how to break free and succeed as you are - Alicia Menendez (New York Harper Business, an imprint of HarperCollins Publishers, 2019)
Consider that even competent women must appear likeable to successfully negotiate a salary, ask for a promotion, or take credit for a job well done?and that studies show these actions usually make them less likeable. And this minefield is doubly loaded when likeability intersects with race, ethnicity, sexual orientation, and parental status.
Includes bibliographical references (pages [209]-225) and index
Keywords: Women--Public opinion